1978
DOI: 10.1002/cne.901800102
|View full text |Cite
|
Sign up to set email alerts
|

Efferent projections of the subthalamic nucleus: An autoradiographic study in monkey and cat

Abstract: The efferent projections of the subthalamic nucleus were studied with the autoradiographic tracing technique in Rhesus monkey and cat. From the data it appears that the major efferent projections of the nucleus are to the pallidal complex and the substantia nigra. In both monkey and cat, the projection to the pallidal complex is truly massive and is directed at both pallidal segments. The projection field includes an infracommissural part of the pallidal complex bordering on the substantia innominata. In the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
90
1
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(97 citation statements)
references
References 16 publications
5
90
1
1
Order By: Relevance
“…Valuable efforts have been made in characterizing the anatomical (29) and electrophysiological (30) properties of neurons within this structure. Recently, Favier et al (31) identified altered protein levels of VGLUT1 and VGLUT2 in multiple brain areas upon STN high-frequency stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Valuable efforts have been made in characterizing the anatomical (29) and electrophysiological (30) properties of neurons within this structure. Recently, Favier et al (31) identified altered protein levels of VGLUT1 and VGLUT2 in multiple brain areas upon STN high-frequency stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…It projects to the internal and external segments of the globus pallidus (Carpenter et al 198 1 a;Groenewegen and Berendse 1990;Nauta and Cole 1978;Parent and Smith 1987;Smith et al 1990) and the substantia nigra pars reticulata (SNr, Canteras et al 1990;Carpenter et al 1968, 198 lb;Kanazawa et al 1976;Nauta and Cole 1978;Parent and Smith 1987;Smith et al 1990), the major output structures of the basal ganglia system. It also projects to the pedunculopontine nucleus (Nauta and Cole 1978;Parent and Smith 1987;Smith et al 1990). Inputs to STN are multiple.…”
Section: Introductionmentioning
confidence: 99%
“…Possible oculomotor functions for STN are suggested by its afferent connections from the cortical eye fields (Huerta and Kaas 1990;Huerta et al 1986;Stanton et al 1988) and its efferent connections to SNr (Nauta and Cole 1978;Parent and Smith 1987;Smith et al 1990). Because STN appears to play an important role in motor control, and damage to STN has been implicated in many movement disorders, its potential role in oculomotor functions is important to establish.…”
Section: Introductionmentioning
confidence: 99%
“…5 In relation to working theories of subcortical participation in language, it has been postulated that the striatum, internal globus pallidus (GPi), and a chain of thalamic nuclei (including the ventral anterior and lateral nuclei, pulvinar, centrum medianum (CM), and nucleus reticularis (NR)) facilitate the activation, integration, transfer, or modulation of cortically generated, context specific linguistic information through cortico-subcortical-cortical circuits. 1 2 7 Evidently, indirect circuitry components-such as external globus pallidus (GPe)-STN, STN-GPe, 8 cortex-STN, 9 GPe-GPi/substantia nigra reticulata (SNr), GPe-NR, 6 centrum medianum-parafascicular complex (CMPFC)-STN, 5 and GPi-CM 10 projections-suggest major ramifications for basal ganglia mediated thalamocortical activity subserving language processes.…”
mentioning
confidence: 99%